High carbon storage in carbon‐limited trees. Issue 1 (15th December 2018) - Weber, Raphael; Gessler, Arthur; Hoch, Günter
Summary: The concentrations of nonstructural carbohydrates (NSCs) in plant tissues are commonly used as an indicator of total plant carbon (C) supply; but some evidence suggests the possibility for high NSC concentrations during periods of C limitation. Despite this uncertainty, NSC dynamics have not been investigated experimentally under long‐term C limitation. We exposed saplings of 10 temperate tree species differing in shade tolerance to 6% of ambient sunlight for 3 yr to induce C limitation, and also defoliated one species, Carpinus betulus, in the third season. Growth and NSC concentrations were monitored to determine C allocation. Shade strongly reduced growth, but after an initial two‐fold decrease, NSC concentrations of shaded saplings recovered to the level of unshaded saplings by the third season. NSC concentrations were generally more depleted under shade after leaf flush, and following herbivore attacks. Only under shade did artificial defoliation lead to mortality and depleted NSC concentrations in surviving individuals. We conclude that, irrespective of shade tolerance, C storage is maintained under prolonged shading, and thus high NSC concentrations can occur during C limitation. Yet, our results also suggest that decreased NSC concentrations are indicative of C limitation, and that additional leaf loss can lead to lethal C shortage in deep shade.